Preparation of glycosylated zein and retarding effect on lipid oxidation of ground pork. (15th July 2017) - Wang, Xiao-Jie; Zheng, Xi-Qun; Liu, Xiao-Lan; Kopparapu, Narasimha-Kumar; Cong, Wan-Suo; Deng, Yong-Ping
Highlights: Zein was modified by enzymatic glycosylation catalyzed by TGase. HPLC and FT-IR analysis were used to confirm the conjunction of chitosan to zein. Glycosylation improved the physico-chemical properties of the modified zein. Glycosylated zein retarded lipid oxidation of ground pork significantly. Abstract: The focus of the present work was to investigate the glycosylation of zein, partial properties of the glycosylated zein (GZ) and its retarding effect on lipid oxidation of ground pork. Zein was glycosylated with chitosan (MW 1500 Da) by microbial transglutaminase, the reaction was verified by FT-IR. Under the optimized conditions, 97.48 mg of glucosamine was covalently conjugated to 1 g of zein, determined by HPLC. The solubility and the surface hydrophobicity of GZ were significantly improved. In vitro studies of GZ showed a dose-dependent scavenging activity against free radicals of DPPH, superoxide and hydroxyl radical, and the EC50 value for DPPH radical was 1.99 μg TE/mg protein. In addition, reducing power and Fe 2+ -chelating capacity of it were 16.60 and 12.96 μg TE/mg protein, respectively. GZ resulted in low levels of thiobarbituric acid-reactive substances and peroxide value of ground pork. These results suggest that GZ is a potential natural antioxidant.